Entre grades invisíveis : a (des) proteção social ao egresso prisional - Rodrigues, Viviane Isabela (2017)
The production "Between invisible grids: A (dis) Prison protection, solidified itself as a qualitative study of an exploratory level that sought to unveil aspects of social protection aimed at detainee prison under the face of the guarantee of social rights in the state of Rio Grande Of the South. The research findings emerged from a field study, which had as subjects of research, ex-prisoners. The data of the study in vogue, illuminated by the critical dialectical analysis of reality and anchored in the Marxist tradition, enabled the unveiling of the scenario of social deprotection to which the prison egress is exposed today. The theoretical and empirical problematizations presented in this study sought to problematize the dynamics of social (dis) protection to the prison egress under the aegis of the conjuncture reading, which runs through the analysis of social protection in recent capitalism, as well as the ideological inference of neoliberalism In the dictates of State policies, as a result of the consequent retraction of the State in the field of guaranteeing rights and the accountability of other social and institutional actors to such guarantees. From this point of view, the analyzes promoted here elucidate the transition from the social state to the criminal state, which socially disseminates punitive ideas rooted in the precepts of criminal selectivity and criminalization of poverty. The criminal issue analyzed here, analyzed from the precepts of critical criminology, helped to construct theoretical assumptions that elucidate preliminarily the propelling factors and the refutations from social deprotection to the prison egress.